2022
DOI: 10.3389/fpubh.2022.778002
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Energy Consumption Revolution on Farmers' Happiness: An Empirical Analysis From China

Abstract: This study divided the impact of energy consumption revolution on farmers' happiness into direct and indirect effects. We empirically tested these effects using the Chinese General Social Survey (CGSS) household data in 2015 and the mediation-moderation model. The results showed that: (1) The rural energy consumption revolution has increased the probability of farmers' happiness level by 22.7%. The direct effects with obvious marginal decrement accounted for the main part (over 90%) of the total effect, but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…This study has the following shortcomings, including the fact that although the indicator of perceived depression in this paper is also widely used in the existing literature, [106][107][108][109][110] it may not be the most effective measure of depression. To enhance the study's findings, it would be beneficial to incorporate other depression indexes based on more reliable scales, as this would enable a more comprehensive understanding of depression within the context of the study, leading to more accurate and reliable conclusions.…”
Section: Limitationmentioning
confidence: 99%
“…This study has the following shortcomings, including the fact that although the indicator of perceived depression in this paper is also widely used in the existing literature, [106][107][108][109][110] it may not be the most effective measure of depression. To enhance the study's findings, it would be beneficial to incorporate other depression indexes based on more reliable scales, as this would enable a more comprehensive understanding of depression within the context of the study, leading to more accurate and reliable conclusions.…”
Section: Limitationmentioning
confidence: 99%
“…Overall, this study illustrates the psychological processes that underlie how power affects happiness and mental illness from a coping viewpoint. Xu and Ge (2022) tested the revolution energy consumption impact on farmer's happiness with empirical analyses in the case of China. The authors studied both direct and indirect effects and the results showed that farmers' happiness has grown by 22.7% thanks to the revolution in rural energy usage, furthermore through the mediating effect of more leisure time, the revolution in rural energy use has marginally raised farmers' happiness; but, the impact of higher use costs on the satisfaction of low-income farmers was virtually significant.…”
Section: Happiness and Electricity Consumptionmentioning
confidence: 99%
“…The main explained variable in this paper is the individual's happiness level, which is used in may existing studies (69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80). This measure is derived from the respondent's response to the question in CGSS: "Do you feel that you are generally happy in your life?"…”
Section: Measuresmentioning
confidence: 99%